2010
DOI: 10.1097/ncc.0b013e3181cfb55a
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Evaluation of an Iyengar Yoga Program for Breast Cancer Survivors

Abstract: Nurses may consider IY as a possible intervention strategy to help breast cancer survivors improve their QoL and psychosocial functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 50 publications
4
52
1
Order By: Relevance
“…These positive initial results indicate the need for a larger, randomized, and controlled study to further evaluate the efficacy of restorative yoga. • Iyengar Yoga: One of the most widely practiced forms of yoga found in the Western world, Iyengar yoga focuses on body alignment [52]. This yoga style has been described as an innovative adaptation for individuals who are stiff, immobile, ill, or injured.…”
Section: Yogamentioning
confidence: 99%
“…These positive initial results indicate the need for a larger, randomized, and controlled study to further evaluate the efficacy of restorative yoga. • Iyengar Yoga: One of the most widely practiced forms of yoga found in the Western world, Iyengar yoga focuses on body alignment [52]. This yoga style has been described as an innovative adaptation for individuals who are stiff, immobile, ill, or injured.…”
Section: Yogamentioning
confidence: 99%
“…[22][23][24] As suggested by our pilot trial, yoga not only may improve pain severity and HR-QOL in women with AIAA, but the improvement in functional outcomes may hold particular clinical relevance for this population as they age, in the context of severe estrogen deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…17 Previous trials of yoga for BCSs, although they showed improved QOL, lacked sufficient objective measures of function. [18][19][20][21][22][23][24] To determine the effects of yoga on AI-related arthralgia, we proposed a pilot study to test the impact of yoga for treatment of AIAA among BCSs. The specific aims of this study were to (1) demonstrate the feasibility of recruitment and retention to a yoga trial, (2) determine the safety of the intervention, and (3) explore the effects of yoga on function, pain, and QOL.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, only a few studies 13,19,21 have evaluated the demographic and psychosocial factors that may affect adherence of breast cancer survivors to yoga intervention. In one study of Iyengar yoga among post-treatment survivors, demographics were not predictive of 12-week adherence, but participants with more advanced tumors or a history of previous cancer adhered better, as did those reporting less fatigue and more happiness at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Among breast cancer survivors, yoga has been associated with reduced arthralgia pain, 9 reduced fatigue and salivary cortisol levels, 10,11 and improved emotional functioning 12 and quality of life. [13][14][15] Trials involving lifestyle interventions often achieve lower adherence than trials involving medications, in part because they require extended motivation and effort on the part of participants. 16 When adherence is lower than expected, participants may receive an insufficient dose of the intervention, biasing the study results toward the null hypothesis.…”
Section: Introductionmentioning
confidence: 99%